2017
DOI: 10.3389/fmicb.2017.01742
|View full text |Cite
|
Sign up to set email alerts
|

Toward an Ecologically Optimized N:P Recovery from Wastewater by Microalgae

Abstract: Global stores of important resources such as phosphorus (P) are being rapidly depleted, while the excessive use of nutrients has led to the enrichment of surface waters worldwide. Ideally, nutrients would be recovered from wastewater, which will not only prevent eutrophication but also provide access to alternative nutrient stores. Current state-of-the-art wastewater treatment technologies are effective in removing these nutrients from wastewater, yet they can only recover P and often in an insufficient way. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
3
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 37 publications
4
32
3
4
Order By: Relevance
“…However, our results show that C. vulgaris needs more nitrogen input than other microalgal species such as Nannochloropsis, Rhodomonas, Isochrysis or Choricystis to render the maximum biomass productivity [56,57]. Notwithstanding, we consider that this characteristic must be considered when using this microalga in wastewater treatments [58][59][60].…”
Section: Discussionmentioning
confidence: 81%
“…However, our results show that C. vulgaris needs more nitrogen input than other microalgal species such as Nannochloropsis, Rhodomonas, Isochrysis or Choricystis to render the maximum biomass productivity [56,57]. Notwithstanding, we consider that this characteristic must be considered when using this microalga in wastewater treatments [58][59][60].…”
Section: Discussionmentioning
confidence: 81%
“…Only in variant 1, series II (50% DLD), the final A. platensis biomass concentration was equal to that measured in control (p > 0.05). Other researchers found the maximum biomass production of Chlorella sorokiniana of 12,000 mg TS/L using anaerobically treated black water as a growth medium [48]. Yang et al [49] achieved the maximum biomass concentration of Chlorella pyrenoidosa of 3.01 g/L using anaerobic digested starch and alcohol wastewaters, while Tan et al…”
Section: Microalgal Growthmentioning
confidence: 98%
“…It should be noted that the N/P ratio affects the microalgae biomass productivity, and the required ratio is strictly dependent on the microalgae species [15]. According to Fernandes et al [48], the green alga Chlorella sorokiniana was able to efficiently remove nutrients from wastewaters with N/P ratios ranging between 15 and 26. In turn, Yu et al [10] indicated the optimal N/P ratio for Chlorella varied between 5 and 15.…”
Section: Nutrient Removal and Digestate Treatment Efficiencymentioning
confidence: 99%
“…Microalgae-based biotechnologies have shown potential applications for advanced treatment of different wastewaters such as municipal wastewater, swine wastewater, poultry litter anaerobic digestate, industrial wastewater, and aquaculture wastewater (Yu et al, 2015;Zhuang et al, 2020). Additionally, microalgae can utilize the nutrients and carbon sources of wastewaters for their cellular metabolisms with generating biomass for production of bioenergy and high value-added compounds (Perez-Garcia et al, 2011;Fernandes et al, 2017). Microalgal treatment of PCs needs further exploration to achieve potential application under current scenario; in particular, more attention should be paid on the development in the performance for removal of nutrients and PCs from real wastewaters.…”
Section: Introductionmentioning
confidence: 99%